Perancangan Desain Sistem Informasi Geografis Pemetaan Desa Mandiri Energi Kec. Pangalengan Kab. Bandung - R. A. E. Virgana Targa Sapanji; Dani Hamdani (Jurnal Manajemen Informatika (JAMIKA), 2020)
Pangalengan District has its uniqueness and uniqueness, such as the height factor, agricultural groups, livestock groups, community plantations or large / state plantations. The problem is that there is no map of the distribution of energy sources in Pangalengan Subdistrict, as many cattle farms almost all have biogas reactors, as well as smallholder plantations that are scattered in almost every village where there is biomass energy potential, lakes such as Cileunca where the water flow is used by around 3 state electricity companies (Indonesia Power) reached the Cikalong area, and there are hundreds of hectares of large / state plantations operating in Pangalengan District, but whether the yield of plantation biomass has been optimized for energy purposes. The method used is geoprocessing to overlay several maps and data so that the data conclusions drawn information, the results of this study in the form of a distribution map of potential biological resources that can be used as an energy source, and the expected impact hopefully the community and government officials in Pangelang District better understand the potential for independent energy in the area.